Allergen-Specific Treg Cells Upregulated by Lung-Stage S. japonicum Infection Alleviates Allergic Airway Inflammation - Li, Zhidan; Zhang, Wei; Luo, Fang; Li, Jian; Yang, Wenbin; Zhu, Bingkuan; Wu, Qunfeng; Wang, Xiaoling; Sun, Chengsong; Xie, Yuxiang; Xu, Bin; Wang, Zhaojun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Schistosoma japonicum infection showed protective effects against allergic airway inflammation (AAI). However, controversial findings exist especially regarding the timing of the helminth infection and the underlying mechanisms. Most previous studies focused on understanding the preventive effect of S. japonicum infection on asthma (infection before allergen sensitization), whereas the protective effects of S. japonicum infection (allergen sensitization before infection) on asthma were rarely investigated. In this study, we investigated the protective effects of S. japonicum infection on AAI using a mouse model of OVA-induced asthma. To explore how the timing of S. japonicum infection influences its protective effect, the mice were percutaneously infected with cercaria of S. japonicum at either 1 day (infection at lung-stage during AAI) or 14 days before ovalbumin (OVA) challenge (infection at post–lung-stage during AAI). We found that lung-stage S. japonicum infection significantly ameliorated OVA-induced AAI, whereas post–lung-stage infection did not. Mechanistically, lung-stage S. japonicum infection significantly upregulated the frequency of regulatory T cells (Treg cells), especially OVA-specific Treg cells, in lung tissue, which negatively correlated with the level of OVA-specific immunoglobulin E (IgE). Depletion of Treg cells in vivo partially counteracted the protective effect of lung-stage S. japonicum infection on asthma. Furthermore, transcriptomic analysis of lung tissue showed that lung-stage S. japonicum infection during AAI shaped the microenvironment to favor Treg induction. In conclusion, our data showed that lung-stage S. japonicum infection could relieve OVA-induced asthma in a mouse model. The protective effect was mediated by the upregulated OVA-specific Treg cells, which suppressed IgE production. Our results may facilitate the discovery of a novel therapy for AAI.